Pulmonary Toxicities Associated With the Use of Immune Checkpoint Inhibitors: An Update From the Immuno-Oncology Subgroup of the Neutropenia, Infection & Myelosuppression Study Group of the Multinational Association for Supportive Care in Cancer - Rapoport, Bernardo L.; Shannon, Vickie R.; Cooksley, Tim; Johnson, Douglas B.; Anderson, Lindsay; Blidner, Ada G.; Tintinger, Gregory R.; Anderson, Ronald (Frontiers in Pharmacology, 2021)
The development of immune checkpoint inhibitors (ICIs) has revolutionized cancer treatment, with agents such as nivolumab, pembrolizumab, and cemiplimab targeting programmed cell death protein-1 (PD-1) and durvalumab, avelumab, and atezolizumab targeting PD-ligand 1 (PD–L1). Ipilimumab targets cytotoxic T lymphocyte-associated antigen-4 (CTLA-4). These inhibitors have shown remarkable efficacy in melanoma, lung cancer, urothelial cancer, and a variety of solid tumors, either as single agents or in combination with other anticancer modalities. Additional indications are continuing to evolve. Checkpoint inhibitors are associated with less toxicity when compared to chemotherapy. These agents enhance the antitumor immune response and produce side- effects known as immune-related adverse events (irAEs). Although the incidence of immune checkpoint inhibitor pneumonitis (ICI-Pneumonitis) is relatively low, this complication is likely to cause the delay or cessation of immunotherapy and, in severe cases, may be associated with treatment-related mortality. The primary mechanism of ICI-Pneumonitis remains unclear, but it is believed to be associated with the immune dysregulation caused by ICIs. The development of irAEs may be related to increased T cell activity against cross-antigens expressed in tumor and normal tissues. Treatment with ICIs is associated with an increased number of activated alveolar T cells and reduced activity of the anti-inflammatory Treg phenotype, leading to dysregulation of T cell activity. This review discusses the pathogenesis of alveolar pneumonitis and the incidence, diagnosis, and clinical management of pulmonary toxicity, as well as the pulmonary complications of ICIs, either as monotherapy or in combination with other anticancer modalities, such as thoracic radiotherapy.